Tramadol dispensing patterns and trends in Canada, 2007‐2016 - Fischer, Benedikt; Kurdyak, Paul; Jones, Wayne (Pharmacoepidemiology and drug safety, 2019)
Purpose Opioid use and associated mortality and morbidity have substantially increased in Canada, which recent interventions have aimed to reduce. Tramadol is an atypical prescription‐only (but unscheduled under Canada's narcotics law) opioid analgesic and not subject to controls for other (eg, strong) opioids. Given experiences in different jurisdictions, tramadol may have been increasingly dispensed as a “substitute” drug during a period with increasingly restrictive controls for other (scheduled) opioids. Methods We examined the annual population‐level retail dispensing (as a proxy for use) of tramadol and (scheduled) “strong opioids” in Canadian provinces for 2007‐2016 based on data from a representative national sample of community pharmacies, covering the majority of episodes of opioid dispensing. Data for both aforementioned formulation categories were converted into defined daily doses (DDD)/1000 population/day and examined descriptively and by segmented regression analyses (to identify significant breakpoints in trends). Results Tramadol use strongly increased in all provinces until 2009. After 2009, tramadol dispensing levels either decelerated their increase or plateaued; “strong opioid” dispensing levels, in comparison, increased strongly until 2011 and decelerated or decreased for the remaining period. Tramadol was consistently dispensed at lower levels than “strong opioids.” Conclusions Tramadol and “strong opioids” showed similar (bifurcated) use trends, with initial increases and subsequent inflections, yet reductions in dispensing occurred earlier for tramadol than for “strong opioids” (the latter occurring following with recent interventions). Distinct from experiences with differential opioid control regimes elsewhere, there is no evidence that tramadol figured as a “substitution” drug for increasingly restricted “strong opioids” in Canada.